The influence of neoliberal policies in the teaching of history, in the last years of elementary school: some thoughts concerning the National Curricular Parameters (PCNs) and the Curricular Common National Basis (BNCC) (Research, Society and Development, 2020)
The text is concerning the influence of neoliberal policies in the teaching of History in the last years of elementary school. It aims at comparing the National Curricular Parameters – PCNs – (BRASIL, 1997) and the Curricular Common National Basis - BNCC – (BRASIL, 2017), with regards to the curricula of the History subject, in elementary school. Looking at this theme, teaching of History and curricular policies, this study based itself in the qualitative research, as the researcher guides his analysis in the interpretation of the real world, paying attention to the hermeneutic character of the task of researching the experiences lived by human beings (LUDKE; ANDRÉ, 1986); (ANDRÉ, 2007). Allied to the bibliographical research, we used the documental analysis LUDKE; ANDRÉ, 1986). Thus,the corpus is built by the theoretical input: Santomé (2003; 2013), Gramsci (2001), Akkari (2011), Gadotti (1983) and Sander (2011),  and by the following documents: Guidelines and Basis of National Education, Law nº 9394/96 (BRASIL, 1996), National Curricular Parameters for Elementary School- History – (BRASIL, 1997) and the Curricular Common National Basis - BNCC – (BRASIL, 2016). The data analysis was supported by the Discursive Textual Analysis (DTA) (MORAES, 2003), in which the methodological proposal is to create an environment of reconstruction, specially to the comprehension of ways of science production and meaning reconstruction of the investigated phenomena. After the data analysis, it was possible to identify three categories: a) the recurrence and intentionality of verbs referring to the teaching of this subject, in the PCNs and the BNCC from the 6th to the 9th years of the before said level of education; b) skills and competences to be developed in these documents; and c) the History contents present in the BNCC and the PCNs. It is concluded that the BNCC is more influenced by the neoliberal policies than the PCNs, once it shows characteristics of a curricular standardization that are more intense and can suggest a refreshment to the stimulus of a critic and reflexive thinking.